Venoms of Centruroides and Tityus species from Panama and their main toxic fractions. (January 2018) - Salazar, Marcos H.; Arenas, Iván; Corrales-García, Ligia L.; Miranda, Roberto; Vélez, Sara; Sánchez, Jairo; Mendoza, Karla; Cleghorn, John; Zamudio, Fernando Z.; Castillo, Adolfo; Possani, Lourival D.; Corzo, Gerardo; et al.
Abstract: The scorpionism in Panama is notorious for the confluence and coexistence of buthid scorpions from the genera Centruroides and Tityus . This communication describes an overview of the larger representative toxic venom fractions from eight dangerous buthid scorpion species of Panama: Centruroides ( C. granosus, C. bicolor, C. limbatus and C. panamensis ) and Tityus ( T. (A.) asthenes, T. (A.) festae, T. (T.) cerroazul and T. (A.) pachyurus ). Their venoms were separated by HPLC and the corresponding sub-fractions were tested for lethality effects on mice and insects. Many fractions toxic to either mice or insects, or both, were found and have had their molecular masses determined by mass spectrometry analysis. The great majority of the lethal components had a molecular mass close to 7000 Da, assumed to be peptides that recognize Na + -channels, responsible for the toxicity symptoms observed in other buthids scorpion venoms. A toxic peptide isolated from the venom of T. pachyurus was sequenced by Edman degradation, allowing the synthesis of nucleotide probe for cloning the correspondent gene. The mature toxin based on the cDNA sequencing has the C-terminal residue amidated, contains 62 amino acid packed by 4 disulfide linkages, with molecular mass of 7099.1 Da. This same toxic peptide seems to be present in scorpions of the species T. pachyurus collected in 5 different regions of Panama, although the overall HPLC profile is quite different. The most diverse neurotoxic venom components from the genus Centruroides were found in the species C. panamensis, whereas T. cerroazul was the one from the genus Tityus. The most common neurotoxins were observed in the venoms of T. festae, T. asthenes and T. pachyurus with closely related molecular masses of 7099.1 and 7332 Da. The information reported here is considered very important for future generation of a neutralizing antivenom against scorpions from Panama. Furthermore, it will contribute to the growing interest in using bioactive toxins from scorpions for drug discovery purposes. Highlights: The venom fractions from eight buthid scorpion species from Panama are described. The primary structure of a toxic peptide isolated from the venom of T. pachyurus was obtained. The most diverse neurotoxic venom components from the genus Centruroides were found in the species C. panamensis. The most diverse neurotoxic venom components from the genus Tityus were found in the species T. cerroazul.